Retrospective study of multiple factors imparting effect on pregnancy outcomes in an in-vitro-fertilization centre - Singh, Preksha T.; Singhvi, Shreyans D.; Kachhia, Utkarsh; Punjabi, Trishala; Punjabi, Shital; Punjabi, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Assisted reproductive technology (ART) cycles include in vitro fertilization of the sperm and ovum and transferring the embryo formed into the uterus of the patients. In ART cycles, there is still a shroud of doubt regarding the pregnancy outcomes of embryo transfer on day 3 versus the embryo transfers on day 5 as well the better pregnancy outcome with fresh versus frozen embryo transfer and the number of embryos transferred. This study is aimed to evaluate these factors and study the way to optimize methods to obtain highest pregnancy outcomes. Methods: A retrospective study was performed of 87 patients who had undergone embryo transfers during the duration of the study from an IVF centre in Ahmedabad. Multiple factors were studied and the clinical outcome was tabulated. The pregnancy outcomes were compared using the values of beta- hcg (human chorionic gonadotropin). The data was compiled and analyzed using Google spreadsheets. To find the statistical difference between different factors- the statistical method of Fischer’s exact test and p-value was used. Results: No statistical difference between day 3 and day 5 embryo transfer as well as between frozen and fresh embryo transfer were both. All of them were found equally efficacious, although 3 and 5 number of embryo transfers were found efficacious. Conclusions: In conclusion authors recommend a day 5 embryo transfer with 3 or 5 embryos which are best-quality frozen or fresh embryos to achieve maximum pregnancy outcomes.